2021
DOI: 10.12688/f1000research.72824.1
|View full text |Cite
|
Sign up to set email alerts
|

Status of self-esteem in medical students of a college in Kathmandu: A descriptive cross sectional study

Abstract: Background: Self-esteem is vital to living a happy, confident and content life. Medical students experience various forms of stress due to academic, financial and social pressures which could affect their levels of self-esteem. This study aims to study the status of self-esteem among undergraduates of a medical college at Tribhuvan University, Nepal. Methods: After receiving the ethical approval from the Institutional Review Committee (IRC) of NAIHS; we conducted a descriptive cross-sectional study among the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Similar results have been observed in another study conducted on medical students in Tribhuvan University, Nepal. In this study, normal self-esteem was observed in 74.4% of the students, and low self-esteem was present in 18.9% [15] . According to two other similar studies, 18% and 19.4% of medical students were found to have low self-esteem [16,17] .…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Similar results have been observed in another study conducted on medical students in Tribhuvan University, Nepal. In this study, normal self-esteem was observed in 74.4% of the students, and low self-esteem was present in 18.9% [15] . According to two other similar studies, 18% and 19.4% of medical students were found to have low self-esteem [16,17] .…”
Section: Discussionmentioning
confidence: 46%
“…This leads to better self-esteem. Various factors, including age, sex, socioeconomic status, family environment, academic stress, and level of study, can influence students' self-esteem [15] . However, no significant association was observed between self-esteem and other sociodemographic variables in our study participants.…”
Section: Discussionmentioning
confidence: 99%